Proteasome inhibition enhances the anti-leukemic efficacy of chimeric antigen receptor (CAR) expressing NK cells against acute myeloid leukemia - Sedloev, David; Chen, Qian; Unglaub, Julia Marie; Schanda, Nicola; Yao, Hao; Besiridou, Eleni; Neuber, Brigitte; Schmitt, Anita; Raffel, Simon; Liu, Yi; Janssen, Maike; Müller-Tidow, Carsten; et al. (Journal of hematology & oncology, 2024)
Relapsed and refractory acute myeloid leukemia (AML) carries a dismal prognosis. CAR T cells have shown limited efficacy in AML, partially due to dysfunctional autologous T cells and the extended time for generation of patient specific CAR T cells. Allogeneic NK cell therapy is a promising alternative, but strategies to enhance efficacy and persistence may be necessary. Proteasome inhibitors (PI) induce changes in the surface proteome which may render malignant cells more vulnerable to NK mediated cytotoxicity. Here, we investigated the potential benefit of combining PIs with CAR-expressing allogeneic NK cells against AML.